Dynamic decision structure and risk taking - Jürgen Eichberger; Werner Güth; Wieland Müller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
This paper investigates the behaviour in repeated decision situations. The experimental study shows that subjects show low or no risk-aversion, but put very high value on the opportunity to sell the lottery in every stage of the decision problem. There is evidence that risk attitudes depend on whether they are measured by comparing the certainty equivalent and the expected value of a lottery or by preferences over mean-preserving spreads.
urn:nbn:de:kobv:11-10046837
Keywords: C9; D8; D9; 330; Dynamic decisions; risk taking behaviour; decision-making experiments